If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + 3x = 0 Solving 11 + 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 3x = 0 + -11 Combine like terms: 11 + -11 = 0 0 + 3x = 0 + -11 3x = 0 + -11 Combine like terms: 0 + -11 = -11 3x = -11 Divide each side by '3'. x = -3.666666667 Simplifying x = -3.666666667
| 4x-29=13+6+2x-18 | | (8x-3)+(-4x+2)= | | -23=3e(-9) | | 3.14-0.45= | | 23=x-6+9+2x-19 | | 3y+6=2x+4 | | 12-(4-3x)=21-(13+7x) | | 10+5x-3y-7x+13+5y= | | 1x+1(4)=3 | | w(4w)=144 | | w(w-4)=144 | | w(4-w)=144 | | 12(0.25)= | | 3g+9-g=17 | | w(w+4)=144 | | 4x^2=-16x-9 | | 8x^2-15x-x^3=0 | | -6(x-9)+3= | | -8x=128 | | 4s-4g=5g | | 2x-10=3y+9 | | -12.20+-6.01= | | 7-5[4-2y-5]= | | 7x+2+8x=32+5x | | 10+y=11 | | 16x^3+54= | | 0.35x=49 | | y-3=2.5(x+1) | | b^2-2b-8=5 | | 19.21-3.06= | | -0.4=V-5 | | (8a+7c)(8a-7c)= |